Consciousness across Sleep and Wake: Discontinuity and Continuity of Memory Experiences As a Reflection of Consolidation Processes - Horton, Caroline L. (Frontiers in Psychiatry, 2017)
The continuity hypothesis (Schredl & Hoffman, 2003) posits that there is continuity, of some form, between waking and dreaming mentation. A recent body of work has provided convincing evidence for different aspects of continuity, for instance that some salient experiences from waking life seem to feature in dreams over others, with a particular role for emotional arousal as accompanying these experiences, both during waking and whilst asleep. However, discontinuities have been somewhat dismissed as being either a product of activation-synthesis, an error within the consciousness binding process during sleep, a methodological anomaly, or simply as yet unexplained. This paper presents an overview of discontinuity within dreaming and waking cognition, arguing that disruptions of consciousness are as common a feature of waking cognition as of dreaming cognition, and that processes of sleep-dependent memory consolidation of autobiographical experiences can, in part, account for some of the discontinuities of sleeping cognition in a functional way. By drawing upon evidence of the incorporation, fragmentation and reorganisation of memories within dreams, this paper proposes a model of discontinuity whereby the fragmentation of autobiographical and episodic memories during sleep, as part of the consolidation process, render salient aspects of those memories subsequently available for retrieval in isolation from their contextual features. As such discontinuity of consciousness in sleep is functional and normal.